Max Weber and Karl Marx - Löwith, Karl, 1897-1973 (Routledge sociology classics., 1993)
Lowith's study of Max Weber and Karl Marx is a key text in modern interpretations of the theme of alienation in Marxist theory and rationalisation in Weber's sociology. It remains the best short student introduction to the differences and comparisons between these essential thinkers. This new edition includes a Preface by Professor Bryan S. Turner which demonstrates the relevance of the book for contemporary sociology.